المراجعة التحليلية كادات لتحسين عملية مراجعة الحسابات في ظل تكنولوجيا المعلومات - تلية, الهام; رزاق بعرة, رميصاء; ناني, يوسف (University of eloued جامعة الوادي, 2017)
This study aims at showing the analytical review and its role in improving accuracy process performance in light of using data technology , thus to encourage clerks in algeria to use analytical reviez in checking out the financial lists which are beneficial in reducing the process danger to the lowest level as well as to increase the clerks commitment in analysis . Many a result have been achieved , among them ; the financial society that is constructed from people , who get benefit from assessment services , agreed on the availability of specialized knowledge in the field of accountability and assessment , and the extent of awareness on the analytical assessment procedures that increase the competency and accuracy process effectiveness and reach its results . Most of the applied methods are: comparing data and financial rates analysis that is considered as the accurate and the easiest methods as for clerks to a neutral outcome. Furthermore , taking into account encouraging auditors to use modern methods in the auditing process, including analytical review in light of using data technology thus , to develop auditing profession in Algeria. key words: Analytical review, Audit , Financial ratios ,Computer Assisted Testing Techniques, Information Technology , Analytical review methods.
مذكرة ماستر تدقيق محاسبي
Keywords: المراجعة التحليلية، مراجعة الحسابات، تكنولوجيا المعلوماتا